In vivo and in vitro antidiabetic effects of aqueous cinnamon extract and cinnamon polyphenol-enhanced food matrix - Cheng, Diana M. (2012)
Cinnamon has a long history of medicinal use and continues to be valued for its therapeutic potential for improving metabolic disorders such as type 2 diabetes. In this study, a phytochemically-enhanced functional food ingredient that captures water soluble polyphenols from aqueous cinnamon extract (CE) onto a protein rich matrix was developed. CE and cinnamon polyphenol-enriched defatted soy flour (CDSF) were effective in acutely lowering fasting blood glucose levels in diet-induced obese hyperglycemic mice at 300 and 600 mg/kg, respectively. To determine mechanisms of action, rat hepatoma cells were treated with CE and eluates of CDSF at a range of 1–25 µg/ml. CE and eluates of CDSF demonstrated dose-dependent inhibition of hepatic glucose production with significant levels of inhibition at 25 µg/ml. Furthermore, CE decreased the gene expression of two major regulators of hepatic gluconeogenesis, phosphoenolpyruvate carboxykinase and glucose-6-phosphatase. The hypoglycemic and insulin-like effects of CE and CDSF may help to ameliorate type 2 diabetes conditions.